Exploring the future of mathematics teaching: Insight with ChatGPT - Edi Supriyadi; K. S. Kuncoro (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
This study aims to provide a comprehensive overview of the future of mathematics teaching from the perspective of ChatGPT, an advanced language processing artificial intelligence (AI) developed by OpenAI. The results of the chat transcripts edited with ChatGPT suggest that the future of mathematics teaching will see the integration of technology and AI to provide personalized learning experiences, blended learning environments, and computational thinking, data literacy, and statistics. Problem-solving, critical thinking, and interdisciplinary connections will continue to be emphasized, and equity and inclusion will remain crucial. AI is expected to revolutionize mathematics education, but thoughtful implementation, ongoing professional development, and pedagogical considerations are essential. However, the future of teaching mathematics will continue to evolve. Therefore, teachers and lecturers need to keep abreast of the latest developments and adapt to them while remaining committed to providing quality teaching.